Optical Character Recognition for Indonesian Electronic Id-Card Image - Sugeng Widodo (IC-ITECHS, 2014)
The need for data from the e-ID card is important, especially as a complement to other information on a computer application system. To retrieve the data from Indonesian ID card to be inserted into the computer application system, it can be done by taking images using such a camera or a scanner, because there is no tool that can be used to retrieve digital data stored on the card. In this way, the image is stored, and can not be used to perform further processing such as data search. OCR is used to convert image data into text, and then the text will be mapped into the database. Image pre-processing done by bileveling, RLSA, and then perform image recognition using template matching.